Public Relations / The Profession and the Practice Third Edition - Aronoff E. Craig; Baskin Otis (Wcb, 1992)
Preface, Public Relations: The Profession, The Nature of Public Relations, Public Relations in Organizational Decision Making, Public Relations: The Process, Planning for Public Relations Effectiveness, Action and Communication, Public Relations: The Public, Media Relations, Consumer Relations and Marketing, Public Relations: The Practice, Public Relations in Government, Corporate Public Relations, Public Relations as a Career, Glossary, Index.
Preface, Public Relations: The Profession, The Nature of Public Relations, Public Relations in Organizational Decision Making, Public Relations: The Process, Planning for Public Relations Effectiveness, Action and Communication, Public Relations: The Public, Media Relations, Consumer Relations and Marketing, Public Relations: The Practice, Public Relations in Government, Corporate Public Relations, Public Relations as a Career, Glossary, Index.